Inhaled Corticosteroid Exposure in Hospitalized Infants with Bronchopulmonary Dysplasia - Leiting, Chelsey; Kerns, Ellen; Euteneuer, Joshua C.; McCulloh, Russell J.; Peeples, Eric S. (American Journal of Perinatology, 2022)
Objective The objective of this paper was to determine inhaled corticosteroid (IC) use in infants with bronchopulmonary dysplasia (BPD), define the interhospital variation of IC administration to infants with BPD, and compare clinical, demographic, and hospital factors associated with IC use.Study Design Using the Pediatric Health Information System database, a retrospective multicenter cohort of 4,551 infants born at <32 weeks of gestation with developing BPD was studied. The clinical, demographic, and hospital characteristics of infants exposed and not exposed to ICs were compared.Results IC use varied markedly between hospitals, ranging from 0 to 66% of infants with BPD exposed to ICs. Increased annual BPD census was not associated with IC use. In total, 25% (1,144 out of 4,551) of patients with BPD and 43% (536 out of 1,244) of those with severe BPD received ICs. Increased IC exposure was associated with lower birth weight and gestational age, days on respiratory support, need for positive pressure ventilation at 36-week postmenstrual age, need for tracheostomy, and increased use of systemic steroids, bronchodilators, and diuretics.Conclusion IC exposure is common in infants with BPD, with substantial interhospital variability. IC use was associated with more severe disease. Hospital experience did not account for the wide variability in IC use by the hospital. Further research into the effects of ICs use is urgently needed to help guide their use in this vulnerable population.Key Points
Keywords: bronchopulmonary dysplasia; inhaled corticosteroids; budesonide; beclomethasone; fluticasone